Experimental investigation on ethane pulsating heat pipe based on Stirling cooler. (April 2018) - Chen, Xi; Shao, Shuai; Xiang, Jiajia; Ma, Wentong; Zhang, Hua
Highlights: An experimental system of ethane pulsating heat pipe (EPHP) was built. The effects of FRs, IAs and HIs on the performance of EPHP were investigated. The heat transfer characteristics of EPHP with 30% FR were studied. The performances of EPHP under anti-gravity condition were tested. Abstract: An experimental system was built to investigate heat transfer characteristics of an ethane pulsating heat pipe (EPHP) based a Stirling cooler. The EPHP is made of copper pipe with an inner diameter of 2 mm, consisting of 20 tubes. The effects of filling ratios (FRs), heat inputs (HIs) and inclination angles (IAs) on the performance of the EPHP were studied under different temperature regions. During the cooling process, the EPHP shows a high heat transfer efficiency. The optimal FR corresponding to the lowest thermal resistance is about 30%. For the same FR, the best heat transfer performance of EPHP is not obtained at IA of 90°, but a specific IA between vertical and horizontal orientation. The thermal resistance increases slowly when the IA increases under anti-gravity condition, but when the IA is close to −90°, the thermal resistance increases rapidly.